An examination of some physiological and instrumental parameters affecting the contraction of circulated mammalian muscle. - Geffen, Laurence Basil (My University, 1963)
The rapid progress of the last decade has made possible the synthesis of the molar and molecular approaches to the mechanism of muscle contraction. It is now possible to offer a molecular explanation for many of the gross mechanical properties of muscle. As a result there is a necessity to re-examine the validity of the classical terminology used to describe these properties, and to define them more accurately. Since Pick (1882), various "types” of contraction have been ascribed to muscle, according to the changes in length and tension of the activated muscle. These are dependent upon the load opposing the muscle. If the load is less than the force developed in the muscle, shortening occurs at a constant tension just exceeding the load. This process is termed isotonic contraction. If, on the other hand, the load is equal to the tension developed in the muscle,there is no overall change in length, although tension in the system rises. This constitutes an isometric contraction. Recently, studies of the ultra-structure and mechanical properties of muscle have revealed inherent difficulties in the classical terminology.
Thesis (Master of Science)--University of the Witwatersrand, Faculty of Health Sciences, 1963.
Keywords: Muscle Contraction; Mammals